Implementing blind proficiency testing in forensic laboratories: Motivation, obstacles, and recommendations - Mejia, Robin (Forensic Sci Int Synerg, 2020)
Regular proficiency testing of forensic examiners is required at accredited laboratories and widely accepted as an important component of a functioning quality assurance program. Yet, unlike in other testing industries, the majority of forensic laboratories testing programs rely entirely on declared proficiency tests. Some laboratories, primarily federal forensic facilities, have adopted blind proficiency tests, which are also used in the medical and drug testing industries. Blind tests offer advantages. They must resemble actual cases, can test the entire laboratory pipeline, avoid changes in behavior from an examiner knowing they are being tested, and are one of the only methods that can detect misconduct. However, the forensic context present both logistical and cultural obstacles to the implementation of blind proficiency tests. In November 2018, we convened a meeting of directors and quality assurance managers of local and state laboratories to discuss obstacles to the adoption of blind testing and assess successful and potential strategies to overcome them. Here, we compare the situation in forensic science to other testing disciplines, identifying obstacles to the implementation of blind proficiency testing in forensic contexts, and proposing ways to address those issues and increase the ecological validity of proficiency tests at forensic laboratories.